IMPLEMENTASI PROGRAM KAMPUNG KB DI JORONG HARAPAN MULYA KECAMATAN TIUMANG KABUPATEN DHARMASRAYA - Eka Mardiana; Sri Rahmadani; Erningsih Erningsih (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The Dharmasraya Regency Government has designated Jorong Harapan Mulya as one of the Quality Family Villages (KB Village). KB Village services in Jorong Harapan Mulya cover several sectors such as health and community social. However, the phenomenon that occurs is that this program has not run as expected, many people do not know about the benefits of KB Village, then there is a lack of human resources to run it. The purpose of this study was to describe the implementation and constraints of implementing the KB Village program in Jorong Harapan Mulya, Tiumang District, Dharmasraya Regency.The theory used in this study is the theory of Structural Functionalism by Robert K, Merton. This research is a qualitative research using descriptive method. Data collection methods are through interviews and observation. Interviews were conducted with 11 informants, the informants in this study were taken using a purposive sampling technique. The data analysis model is through the stages of data collection, data reduction, data presentation and drawing conclusions.From the results of the study it was explained that the implementation of the KB Village program in Jorong Harapan Mulya had not been able to run optimally. This is because of the 7 KB village programs, only 4 were implemented. Implementing the KB Kampug program in Jorong Harapan Mulya is still having problems or experiencing obstacles. Such as a lack of understanding or response from the community. In addition, the resources used are still inadequate. The resources in question are in the form of funds, facilities and infrastructure. For example, funds for carrying out activities are available from the district and also from jorong. In addition to funds, there are also infrastructure facilities, for example, Jorong itself provides a place when socialization or meetings take place in Jorong, using the house of the cadres and the working group alternately. Should have a KB village program house that is settled without having to move around